ENHANCING CYBERSECURITY AND LEGAL INTEGRATION: REFORMING INDONESIA'S CYBER LAW TO FOSTER SUSTAINABLE GROWTH IN THE DIGITAL ECONOMY - Widayanti, Tri Fenny; Rohman, Aditya Dwi; Haris, A. Nuril Zamharir; Djafar, Eka Merdekawati; Hakim, Muhammad Zulfan (Diponegoro Law Review, 2025)
The rapid advancement of digital technologies has reshaped the global economy, with the digital economy becoming a key driver of growth and innovation. Indonesia, as the leader in Southeast Asia’s digital economy, has immense potential, with projected growth at 40% by 2018. However, the country’s digital economy remains hindered by an inadequate and fragmented cyber law framework. The existing laws are sector-specific, leading to overlapping institutional authority, weak enforcement, and a lack of clarity in jurisdiction, particularly regarding cross-border cyber threats. This fragmented legal landscape impedes the integration of Indonesia’s digital economy and undermines cybersecurity efforts. This study examines the challenges within Indonesia’s current cyber law and argues for comprehensive reforms to provide clear institutional authority, enhance inter-agency coordination, and create laws tailored to the digital economy and cybersecurity. Drawing insights from international frameworks, such as the European Union's General Data Protection Regulation (GDPR) and Australia's Critical Infrastructure Bill, the study advocates for a dual approach—ensuring both data privacy and critical infrastructure protection. Furthermore, the research highlights the need for collaboration between government, the private sector, and civil society, along with public education initiatives, to foster a secure and trustworthy digital ecosystem. By analyzing existing regulations and proposing targeted reforms, this study aims to contribute to improved cybersecurity governance, enabling sustainable digital transformation and economic growth in Indonesia.